Association among anti-citrullinated protein antibody status, erosive disease and healthcare resource utilization in patients with rheumatoid arthritis. (1st February 2020) - Harrold, Leslie R.; Shan, Ying; Connolly, Sean E.; Alemao, Evo; Rebello, Sabrina; Guo, Lin; Kremer, Joel M.
Abstract: Objective: To characterize the rate of healthcare resource utilization (HCRU) between anti-cyclic citrullinated peptide (CCP; a surrogate for anti-citrullinated protein antibodies [ACPAs]) positive (+) patients with rheumatoid arthritis (RA), either with or without erosions, who initiated biologic disease-modifying antirheumatic drug (bDMARD) treatment. Methods: Data from the Corrona RA registry, a prospective registry of adult patients with RA from 177 sites across 42 states in the US, were analyzed. Annual rates of HCRU (measured based on rates of all-cause hospitalization, joint surgery, imaging procedures and use of assistive devices) were estimated in anti-CCP + patients with and without erosions following bDMARD initiation using a Poisson regression model. Results: Among the 3333 patients with known anti-CCP and erosion status and 12-month post-bDMARD follow-up information in the Corrona registry, 2047 were anti-CCP + and included in this analysis; 868 with and 1179 without erosions. Baseline characteristics were generally well balanced between patients with and without erosions; however, those with erosions had a longer mean RA duration and a higher prior DMARD use. Over 12 months, among anti-CCP + patients, those with erosions had significantly higher rates of all HCRU, except joint surgery, than those without erosions. Age-adjusted risk ratios (95% confidence interval) were as follows: all-cause hospitalization, 1.47 (1.14, 1.90); all-cause imaging, 1.25 (1.03, 1.53); and assistive device use 1.12 (1.00, 1.25). The rate of joint surgery visits was also numerically higher in patients with versus without erosion. Conclusions: ACPA seropositivity with erosive disease was associated with higher rates of HCRU compared with seropositivity without erosions. These findings suggest that providers may want to manage anti-CCP + patients aggressively to achieve better disease control to prevent the development of erosions and the associated increase in HCRU.